2020
DOI: 10.3390/brainsci10100710
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Auditory Processing Deficits after Cochlear Synaptopathy Depend on Auditory Nerve Latency and the Ability of the Brain to Recruit LTP/BDNF

Abstract: Age-related decoupling of auditory nerve fibers from hair cells (cochlear synaptopathy) has been linked to temporal processing deficits and impaired speech recognition performance. The link between both is elusive. We have previously demonstrated that cochlear synaptopathy, if centrally compensated through enhanced input/output function (neural gain), can prevent age-dependent temporal discrimination loss. It was also found that central neural gain after acoustic trauma was linked to hippocampal long-term pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 95 publications
(164 reference statements)
5
25
0
Order By: Relevance
“…Fast auditory processing is also suggested to be essential for memory-dependent central auditory adjustment processes following enriching sound exposure ( SE ) or auditory deprivation ( Matt et al, 2018 ; Knipper et al, 2020 ). Accordingly, long-term plasticity changes following SE or auditory deprivation can be monitored through altered levels of activity-regulated cytoskeleton-associated protein ( Arc/Arg3.1 ; here: Arc ) and parvalbumin ( PV ) in the AC and hippocampus and through correlating changes in long-term potentiation ( LTP ) in hippocampal CA1 pyramidal neurons ( Matt et al, 2018 ; Marchetta et al, 2020 ). Therefore, sound-induced adjustment processes are likely to be reflected by altered plasticity changes in the AC and hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Fast auditory processing is also suggested to be essential for memory-dependent central auditory adjustment processes following enriching sound exposure ( SE ) or auditory deprivation ( Matt et al, 2018 ; Knipper et al, 2020 ). Accordingly, long-term plasticity changes following SE or auditory deprivation can be monitored through altered levels of activity-regulated cytoskeleton-associated protein ( Arc/Arg3.1 ; here: Arc ) and parvalbumin ( PV ) in the AC and hippocampus and through correlating changes in long-term potentiation ( LTP ) in hippocampal CA1 pyramidal neurons ( Matt et al, 2018 ; Marchetta et al, 2020 ). Therefore, sound-induced adjustment processes are likely to be reflected by altered plasticity changes in the AC and hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…These adjustment processes can be monitored through altered levels of excitatory (activity-regulated cytoskeleton-associated protein) and inhibitory parvalbumin marker proteins in the auditory cortex and hippocampus. Furthermore, these molecular changes were correlated with changes in LTP in hippocampal CA1 pyramidal neurons (Marchetta, Savitska, et al, 2020;Matt et al, 2018). Therefore, sound-induced adjustment processes are likely to be reflected in altered plasticity changes, not only in central auditory nuclei, but also in associated brain regions like the hippocampus.…”
Section: Role Of Cgmp Signalling In Central Auditory Plasticity Responsesmentioning
confidence: 96%
“…Thus, studies analyzing aging animals showed that, independently of age or hearing thresholds, animals fell into two groups regarding central auditory responses to cochlear synaptopathy: The ‘high-compensating’ group was able to respond to cochlear synaptopathy with an enhanced input/output function (elevated ABR wave IV/I ratio), linked with enhanced LTP and maintained temporal processing ( Eckert et al, 2021 ) ( Figure 7A , left panel). The other, the ‘low-compensating’ group, exhibited weakened compensatory capacity (lower ABR wave IV/I ratio), linked with lower LTP, and weakened temporal coding ( Marchetta et al, 2020 ) ( Figure 7B , right panel). The reduced capacity to centrally compensate age-dependent cochlear synaptopathy, and the lower hippocampal LTP with attenuated temporal coding, was associated with a prolonged latency of the auditory nerve response (ABR wave I) in comparison to the high-compensating group ( Marchetta et al, 2020 ), suggesting that fast (high-SR) auditory processing was mitigated in this group.…”
Section: Altered Excitation and Inhibition Following Diminished Fast Auditory Processing Linked To ‘Central’ Hearing Lossmentioning
confidence: 99%